An Asset Based Approach (ABA) toward Self-Sustaining Mission in Indonesia - Daniel Trihandarkha (Predica Verbum: Jurnal Teologi dan Misi, 2021)
Pandemic is virtually unprecedented. Churches and mission works alike are forced to think differently on how they do their respective work. With the restrictions of gathering in big groups and the economic crisis crippled the market, the mission works also suffers in what already difficult environment in Indonesia. The voices of restlessness seeing how oblivious we are in the state complacencies are finally being heard in the time of crisis, namely, pandemic. This is the time we need to listen to the Spirit and Truth to understand the sign time. In the midst of this difficult time missions are not required to look elsewhere but surrounding. It is a pathway to discover, not invent, the God given assets in next door neighbor, and that’s what Asset Based Approach (ABA) is all about, contributing to the self-sustaining mission in the long run.